CHARACTERIZATION OF SOME GENERATIVE PHASES OF BLACK RICE ORIGIN OF WEST KALIMANTAN ON RED YELLOW PODZOLIC SOIL - Hearnes Napitupulu; Wasi'an Wasi'an; Fadjar Rianto (Jurnal Sains Pertanian Equator, 2018)
Characterization of black rice is needed to know the character information of the plant. This study aims to determine the generative phase morphology characteristic and the level of similarity of some black rice from West Kalimantan on RYP soil. This research was conducted in experimental garden of Faculty of Agriculture of Tanjungpura University. The study used Completely Randomized Design (CRD), consisting of 4 treatments A = Nanga Taman, B = Sanggau, C = Senakin and D = Ensalang. Each treatment were replicated 6 times and each replication consisted of 3 plant samples.  The observed  measurement were stem strength, plant height, leaf maturity (yellowing), panicle emergence, grain fertility, plant age, leaf color, number of productive tillers, stem color, number of grain per panicle, pannicle type, secondary panicle, males, lemma and palea, hair on lemma and palea, color of grain tip, grain tip, grain end, long grain, diameter of stem segment, length of panicle, seed width and weight of 100 grains. Character observation data were analyzed using MVSP program to obtain dendogram. Based on the analysis of generative phase character, the plant was divided into 3 groups. The first group consists of Senakin black rice. The second group consisted of the black rice species of Ensalang and Sanggau. The third group consists of Nanga Taman black rice.